Reconciling verses and narratives in Zihar judgment - Study and Analysis - - Muhammed Shareef Muhammed Othman (Zanco Journal of Humanity Sciences)
This research involves an analytic study for the Quranic verses in the chapter (Sura) of Almujadala (the pleading woman), about the divine verdict about Zihar, which means (divorcing women by calling them mothers) after a man named Aws Bin Al-Samit pronounced Zihar to his wife. The study explaines the concept of Zihar before Islam and then the divine verdict about it after Islam. This research aims at clearing the confusion about the matter of Zihar that remaineda controversial issue amongst the Islamic law scientist and scholars. This research reached the result that the reason of that long controversy is that there are different stories and Islamic traditional texts that dealt with the issue, that were not quite identical with the obvious meaning of the Quranic verses that descended by Allah to show the divine verdicts about Zihar. But once all the relevant traditional Islamic texts were collected and compared to each other along with the analysis of the verses related to the issue and the time frame in which each one of them was descended, it became clear that those verses were sent in two different times since he ( Aws Bin Al-Samit) divorced his wife (with the pronunciation of Zihar) twice. The first and the second verses were descended in first time he pronounced Zihar to his wife to show and inform the Muslims about the verdict of the act, and the third and fourth verses were descended in the second time to assure and promise torture and severe punishment to those who trespass and violate Allah’s verdicts after they were made clear in the first two verses.